A Study on Conflict Modification in the Novel I am Number Four and its Film Adaptation - Maria Novianti; Safrina Noorman (Universitas Pendidikan Indonesia (UPI), 2022)
The present study entitled A Study on Conflict Modification in the Novel “I Am Number Four” and its Film Adaptation aims to investigate how conflicts affect the characterization of John Smith in the novel and the film adaptation. The study used a qualitative approach with textual analysis since the focus of the study is the conflicts identified in a form of text in the novel and dialogues in the film adaptation. Framed by the theory of adaptation (Hutcheon, 2006), the study found that even though the identified conflicts in the novel are the same as the identified conflicts in the film adaptation, they were still developed differently because of the dramatization done to the conflicts in the film adaptation, resulting in resolutions that are more violent. By reducing peace, distilling violence and adding violence, the identified conflicts in the film adaptation were modified into conflicts which made the characterization of John Smith more violent-looking, aggressive, unstable, and reckless compared to John Smith in the novel.Keywords: Adaptation; Characterization; Conflict